Novel Considerations about Diabetes Management Strategies in Chinese Immigrants in America: Possible Corollaries of the Use of Traditional Chinese Medicines - Julia A Devonish; Supreet Singh; Emilie Tomkinson; Gene D Morse (INNOVATIONS in Pharmacy, 2017)
Worldwide, the prevalence of type 2 diabetes mellitus (T2DM) and its related management costs have increased over time. The latest predictions anticipate this trend to continue during the next few decades. As individuals with T2DM in the United States (US) are burdened with escalating prescription drug expenses, the appeal and use of cost effective alternatives may also increase. Herbal supplements are an example of such an alternative, but are unregulated and mostly lacking scientific evidence of advertised claims. In general, plant based herbal preparations are often advertised as ‘natural’, ‘less-toxic’, ‘medicines’ and are widely available from public retailers throughout the country. Over half of the US adult population report the use of supplements. Eastern countries, and especially China, have a long history of the use of herbal preparations as traditional medicine to prevent and treat diabetes. Recently the US has experienced a growth in the number imports of herbal supplements and other Traditional Chinese Medicines (TCM) to the country as well as the most rapid population growth in individuals who identify themselves as Asian. To date, little is known about the prevalence TCM use in the management of T2DM either alone or in combination with prescription medicines in the US. Knowledge of possible implications to patient safety (e.g., interactions, adverse effects) with concurrent use of both TCM and prescription medicines is also lacking. This review begins with summaries of the T2DM management strategies employed in traditional modern medicine (TMM) and Chinese medicine (TCM). A review of literature follows where the most commonly used TCM herbal preparations and their ingredients are identified and found along with any published reports of their proposed mechanisms of action, efficacy, adverse effects, and contraindications.